IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN AKTIVITAS BELAJAR DI SMPN 2 TELUKJAMBE TIMUR - Ahmad Shofi; Camelyati Kulsum Fadilah; Farah Nurfadilah; Tika Mutiasari (Jurnal Tawadhu, 2024)
The learning model is the most important factor in the learning process because the learning model is a plan that helps the learning process to be carried out in accordance with the learning objectives. Therefore, it is necessary to apply a learning model to facilitate the learning process. SMPN 2 Telukjambe Timur applies a cooperative learning model to improve students' learning activities in training cohesiveness in a group as well as improving skills in students. Cooperative learning models are applied in various aspects of learning, especially in Islamic Education (PAI) lessons. This cooperative learning model involves the activeness of students in forming their own groups, this aims to hone and train students in developing their abilities in terms of cognitive and psychomotor. This article is made with qualitative methods and literature studies and data collection techniques through interviews and observations. This research aims to find out the effectiveness of this learning model and how Islamic Religious Education teachers implement cooperative learning models in the school environment and in the classroom.